Advances in diagnostic imaging for peripheral arterial disease. (October 2010) - Tang, Gale L; Chin, Jason; Kibbe, Melina R
Refinements in both noninvasive and invasive imaging techniques have led to significant improvements in both the diagnosis and treatment of peripheral arterial disease. Multiple complementary imaging modalities are available for evaluating these patients. This article reviews the advantages, disadvantages and recent advances in the commonly used clinical applications of duplex ultrasonography, magnetic resonance angiography, computed tomographic angiography, digital subtraction angiography and intravascular ultrasound for arterial imaging in the lower extremities. It also discusses experimental imaging techniques more recently applied to peripheral arterial disease such as PET, hyperspectral imaging and molecular imaging of atherosclerosis. As more is understood about both lesion and patient characteristics that affect their response to peripheral interventions, clinician selection of the various imaging modalities as well as different peripheral interventions will allow for more effective treatment of patients with peripheral arterial disease.